Design, synthesis and biological evaluation of novel 5-hydroxy-2-methyl-4H-pyran-4-one derivatives as antiglioma agents. Issue 3 (7th February 2018) - Li, Yi-Bin; Hou, Wen; Lin, Hui; Sun, Ping-Hua; Lin, Jing; Chen, Wei-Min
Abstract : Two series of 5-hydroxy-2-methyl-4 H -pyran-4-one derivatives were synthesized and their antiglioma activities were evaluated. Abstract : d -2-Hydroxyglutarate (d -2HG) is frequently found in human brain cancers. Approximately 50–80% of grade II glioma patients have a high level ofd -2HG production, which can lead to cancer initiation. In this study, a series of novel 5-hydroxy-2-methyl-4 H -pyran-4-one derivatives were designed and synthesized as antiglioma agents, and their related structure–activity relationships are discussed. Among these novel compounds, 4a exhibited promising anti-proliferative activity against glioma HT1080 cells and U87 cells with an IC50 of 1.43 μM and 4.6 μM, respectively. Further studies found that the most active compound (4a ) shows an 86.3% inhibitory rate against the intracellular production ofd -2HG at 1 μM, and dramatic inhibitory effects, even at 1 μM on the colony formation and migration of U87 and HT1080 cells.